Evaluation of anterograde amnesia after the use of midazolam and valerian-hops in anxious individuals undergoing mandibular third molar extraction in a slipt-mouth, triple-blind, randomized clinical trial (Research, Society and Development, 2022)
This prospective, split-mouth, triple-blind, randomized clinical trial aimed to assess whether there was anterograde amnesia when performing minimal conscious sedation with fixed extract of valerian-hops and midazolam in anxious individuals who underwent tooth extractions impacted lower third molars. The study was completed by 23 individuals aged between 18 and 25 years, of both sexes, with ASA I surgical risk classification and with impacted lower third molars positioned in a similar way bilaterally. The surgical interventions were performed by a single specialist in oral and maxillofacial surgery and traumatology, in two different sessions, with an interval of 21 days between them. Before all surgeries, each participant received an 8 mg dexamethasone capsule. Forty-five minutes before surgery, they randomly received, orally, 1 capsule of Valerian 500 mg – Hops 120 mg or midazolam 15 mg for each side to be operated on. Each participant received 12 acetaminophen 750 mg tablets to take, if needed, postoperatively. A questionnaire was used to analyze anterograde amnesia. Our results showed that midazolam presented better results in relation to anterograde amnesia. We conclude that valerian-hops is not effective in relation to anterograde amnesia, but it manages to establish comfort, few hemodynamic changes and few side effects, being an alternative to be used in the preoperative period of anxious patients who need lower third molar extraction.